Mulk Raj Anand’s Innovative Views: A Critical Review: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Every great author writes about his age, its rich beauties wonders, nuisances, awesome absurdities and chilling woes. He has his own creed in art. It involves his views, opinions and principles given on a wide range of issues. There are certain events, incidents and situations too that also leave their impact him. Mulk Raj Anand is such an author, as fittingly distinguishes himself in relation to his age. The close contact of human life around him in all its contrasting forms gives him an immense variety of experience which, in turn, helps formulate his overall mindset fairly called an author’s ‘Literary Creed’. Time is a great teacher as it affects inevitably everything and nearly every human being coming across within its omnipotent sway. An artist is supposed to sharply react to the beats of his times so that he could try to explain to the best of his satisfaction the hazy puzzles and riddles of human life confronting before his eyes in all their crude extremes- good and bad ,beautiful and ugly, weak and strong ,sweet and bitter etc.